Three new species of the genus Synagelides Strand, 1906 (Araneae, Salticidae) from Yunnan, China - Li, Bing; Cheng, Yi; Wang, Qi; Yang, Sufang; Peng, Xianjin (Zootaxa, 2023)
Three new species of Synagelides Strand, 1906 (Araneae, Salticidae) from Yunnan, China are described: S. furcatoides sp. nov. (♂♀), S. furcatus sp. nov. (♂) and S. montiformis sp. nov. (♂♀). Photographs of the habitus and copulatory organs as well as a distribution map are provided.